2022
DOI: 10.3390/microorganisms10010165
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol Potential of Chitin and Chitosan Extracted from Black Soldier Fly Pupal Exuviae against Bacterial Wilt of Tomato

Abstract: Globally, Ralstonia solanacearum (Smith) is ranked one of the most destructive bacterial pathogens inducing rapid and fatal wilting symptoms on tomatoes. Yield losses on tomatoes vary from 0 to 91% and most control measures are unaffordable to resource-poor farmers. This study investigated the antimicrobial activities of chitin and chitosan extracted from black soldier fly (BSF) pupal exuviae against R. solanacearum. Morphological, biochemical, and molecular techniques were used to isolate and characterize R. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Kemboi et al . 69 tested chitosan from pupal exuviae of Hermetia illucens on Ralstonia Solanacearum, using disc diffusion test at the similar concentration range. Both obtained larger inhibition diameters than ours, but at much higher concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Kemboi et al . 69 tested chitosan from pupal exuviae of Hermetia illucens on Ralstonia Solanacearum, using disc diffusion test at the similar concentration range. Both obtained larger inhibition diameters than ours, but at much higher concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The exogenous chitin of pure chitin (PC) and crude chitin (CC) were purchased from Jinan Apollo Crustacean Fertilizer Co., Ltd. and Shanghai Haike Shengwu Biotech Co., Ltd., respectively, and were used to assess the effectiveness of exogenous chitin on continuous cropping obstacles. Crude chitin is a biopolymer ( Debode et al., 2016 ; Zhan et al., 2021 ) that is mainly sourced from the shells of marine organisms, such as shrimp, lobsters and crabs, while pure chitin is purified from crude chitin by removing calcium and protein with acid and alkali ( Inderbitzin et al., 2018 ; Kemboi et al., 2022 ). The total carbon and nitrogen contents were 187.7 g/kg and 31.5 g/kg in pure chitin and 396.3 g/kg and 72.4 g/kg in crude chitin, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Organic amendments are known to be attractive alternatives to relieve continuous cropping obstacles ( Zhou et al., 2021 ). Chitin, as the most abundant polysaccharide in nature, possesses good biocompatibility, biodegradability, nontoxicity and various biological activities and poses no hazard to the environment ( Zhan et al., 2021 ; Kemboi et al., 2022 ). More importantly, chitin also has great potential for improving soil quality, inducing plant disease resistance and promoting plant growth ( Fan et al., 2020b ; Shamshina et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…An example in agriculture is chitin which promotes not only human and animal health, but also plant health. Chitin and chitosan recovered from the pupal shells of the black soldier fly and used as soil amendment show an ability to control bacterial wilt of tomato caused by Ralstonia solanacearum (Kemboi et al 2022). Barrágan-Fonseca et al (2022) found that residual streams from insect farming, such as frass and exuviae (containing chitin and other compounds), stimulate beneficial soil microbes that induce systemic plant resistance.…”
Section: Nutrition and Healthmentioning
confidence: 99%
“…Chitin and chitosan recovered from the pupal shells of the black soldier fly and used as soil amendment show an ability to control bacterial wilt of tomato caused by Ralstonia solanacearum (Kemboi et al . 2022). Barrágan‐Fonseca et al .…”
Section: Nutrition and Healthmentioning
confidence: 99%